Analysis of the Values of Religious Moderation in Islamic Religious Education and Character Education Textbooks for class V Elementary School, Merdeka Curriculum (An Naba, 2024)
The teaching of the values of religious moderation needs to be instilled from an early age, especially starting through basic education. One strategy for religious moderation education is to include these moderation values in the components of teaching materials. Islamic Religious Education subjects are the right means to introduce and teach to become Muslims who uphold religious moderation. This research aims to analyze the values of religious moderation in Islamic Religious Education and Character Education textbooks for class V elementary school which were published in 2021 and are based on the Independent Curriculum. The approach used is literature study and content analysis. The results of this research show that of the ten chapters and their sub-discussions, there are nine chapters that contain the values of religious moderation in them, both in the description of the material and the illustrative images contained therein. There are nine values of moderation contained, including: tolerance, finding a middle way, upright and fair, pioneering, deliberation, improvement, non-violence, culturally friendly, and love of the country.